The clinical and therapeutic profiles of prolactinomas associated with germline pathogenic variants in the aryl hydrocarbon receptor interacting protein (AIP) gene - Vroonen, Laurent; Beckers, Albert; Camby, Severine; Cuny, Thomas; Beckers, Pablo; Jaffrain-Rea, Marie-Lise; Cogne, Muriel; Naves, Luciana; Ferriere, Amandine; Romanet, Pauline; Elenkova, Atanaska; Karhu, Auli; et al. (Frontiers in Endocrinology, 2023)
Prolactinomas are the most frequent type of pituitary adenoma encountered in clinical practice. Dopamine agonists (DA) like cabergoline typically provide signs/symptom control, normalize prolactin levels and decrease tumor size in most patients. DA-resistant prolactinomas are infrequent and can occur in association with some genetic causes like MEN1 and pathogenic germline variants in the AIP gene (AIPvar). We compared the clinical, radiological, and therapeutic characteristics of AIPvar-related prolactinomas (n=13) with unselected hospital-treated prolactinomas ("unselected", n=41) and genetically-negative, DA-resistant prolactinomas (DA-resistant, n=39). AIPvar-related This is a provisional file, not the final typeset article prolactinomas occurred at a significantly younger age than the unselected or DA-resistant prolactinomas (p<0.01). Males were more common in the AIPvar (75.0%) and DA-resistant (49.7%) versus unselected prolactinomas (9.8%; p<0.001). AIPvar prolactinomas exhibited significantly more frequent invasion that the other groups (p<0.001) and exhibited a trend to larger tumor diameter. The DA-resistant group had significantly higher prolactin levels at diagnosis than the AIPvar group (p<0.001). Maximum DA doses were significantly higher in the AIPvar and DA-resistant groups versus unselected. DA-induced macroadenoma shrinkage (>50%) occurred in 58.3% in the AIPvar group versus 4.2% in the DA-resistant group (p<0.01). Surgery was more frequent in the AIPvar and DAresistant groups (43.8% and 61.5%, respectively) versus unselected (19.5%: p<0.01). Radiotherapy was used only in AIPvar (18.8%) and DA-resistant (25.6%) groups. AIPvar confer an aggressive phenotype in prolactinomas, with invasive tumors occurring at a younger age. These characteristics can help differentiate rare AIPvar related prolactinomas from DA-resistant, genetically-negative tumors.